2009
DOI: 10.2190/wr.14.3.g
|View full text |Cite
|
Sign up to set email alerts
|

Nepali Female Migrants and Informalization of Domestic Care Work: Service or Servitude?

Abstract: Nepali female migrants are among the fastest-growing immigrant workforces in the South Asian community, particularly in service and domestic work in big cities of the United States. However, there has not until now been a study investigating the work experiences of Nepali immigrants/migrants employed in the service and domestic sectors in these cities. This article investigates the work experiences of Nepali female migrants who work in service and domestic/child care work in Boston and New York, focusing on ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…While this need may not be exaggerated, it seems that the link to the class structure still remains even in ‘modern’ societies. Furthermore, previous micro-level studies on the status of domestic workers conclude that class inequalities between employers and employees intersect closely with other inequalities related to gender, ethnicity and nationality, making the power relations in female and migrant dominated domestic work sector particularly unbalanced (for example, Parreñas, 2000; Ehrenreich and Hochshild, 2002; Gurung, 2009; Lutz, 2011; Gavanas, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…While this need may not be exaggerated, it seems that the link to the class structure still remains even in ‘modern’ societies. Furthermore, previous micro-level studies on the status of domestic workers conclude that class inequalities between employers and employees intersect closely with other inequalities related to gender, ethnicity and nationality, making the power relations in female and migrant dominated domestic work sector particularly unbalanced (for example, Parreñas, 2000; Ehrenreich and Hochshild, 2002; Gurung, 2009; Lutz, 2011; Gavanas, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly suggest that the diverse backgrounds and situations of domestic and care workers shape their capabilities and possibilities to influence their income and working conditions. Several other studies support these findings, arguing that the individual characteristics of the worker may influence the bargaining power related to the job, and thus improve their working conditions (Anderson 2000;Gurung 2009;van Walsum 2011). Migrant care workers, especially undocumented migrants, are often identified as a disadvantaged group in the labor markets (Anderson 2010;Behtoui et al 2016;Parreñas Salazar 2000;Shutes and Walsh 2012).…”
Section: Previous Research On Precarious Employment In Domestic and C...mentioning
confidence: 88%
“…Ashforth and Kreiner (1999) contended that being isolated and cut off from any form of support usually led dirty workers to exit their occupation. In the case of migrant Nepali domestic/care workers, Gurung (2009) observed that when the emotional abuse, harassment and exploitation and consequent feelings of vulnerability, risk, inferiority and despair became unbearable, Nepali migrant women working in the USA quit their job as a last resort. Though exiting deprived workers of their livelihood, it provided respite from mistreatment.…”
Section: Engaging Taint Management Strategies To Address Workplace Bullying Emotional Abuse and Harassmentmentioning
confidence: 99%